Third Millennium Figurative Paintings in the Euphrates Valley. A Reassessment - Nunn, Astrid (Ash-sharq: Bulletin of the Ancient Near East – Archaeological, Historical and Societal Studies, 2019)
The paper deals with figurative paintings of the Euphrates valley, including Syria and Turkey, in the third mill. BCE. The little standardised manner of their composition and free distribution of the elements within the picture has links to the Neolithic period, but stands in strong contrast to Mesopotamia. Thus imagery and style strongly distinguish paintings from seals of the same period. These wealthy cities can be regarded as a transitional zone between Syrian and Mesopotamian traditions as exemplified by the Ninkhursag Temple and the Chapel 132 both located in Mari.